2011
DOI: 10.1111/j.1365-3040.2011.02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Hg with phytochelatins is important for plant Hg tolerance

Abstract: Three-week-old alfalfa (Medicago sativa), barley (Hordeum vulgare) and maize (Zea mays) were exposed for 7 d to 30 mM of mercury (HgCl2) to characterize the Hg speciation in root, with no symptoms of being poisoned. The largest pool (99%) was associated with the particulate fraction, whereas the soluble fraction (SF) accounted for a minor proportion (<1%). Liquid chromatography coupled with electro-spray/time of flight mass spectrometry showed that Hg was bound to an array of phytochelatins (PCs) in root SF, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 58 publications
10
94
1
Order By: Relevance
“…An increase in GR activity was also noticed in Phaseolus vulgaris and Alyssum following exposure to Cd (Chaoui et al 1997). Higher synthesis of PCs for Pb alone or in combination to EDTA was also reported earlier in Vallisneria spiralis, Hydrilla and alga Stichococcus bacillaris exposed to Pb, Cd and Hg (Gupta et al 1999;Pawlik-Skowron´ska 2002) and in higher plants of Zea mays and Hordeum vulgare (Carrasco-Gil et al 2011). Interestingly, the burst of PC biosynthesis induced by Pb is also here accompanied by a transient depletion of cell GSH pools that may be perceived by plants as indicating an additional need for sulphur (Nocito et al 2007;).…”
Section: Discussionsupporting
confidence: 63%
“…An increase in GR activity was also noticed in Phaseolus vulgaris and Alyssum following exposure to Cd (Chaoui et al 1997). Higher synthesis of PCs for Pb alone or in combination to EDTA was also reported earlier in Vallisneria spiralis, Hydrilla and alga Stichococcus bacillaris exposed to Pb, Cd and Hg (Gupta et al 1999;Pawlik-Skowron´ska 2002) and in higher plants of Zea mays and Hordeum vulgare (Carrasco-Gil et al 2011). Interestingly, the burst of PC biosynthesis induced by Pb is also here accompanied by a transient depletion of cell GSH pools that may be perceived by plants as indicating an additional need for sulphur (Nocito et al 2007;).…”
Section: Discussionsupporting
confidence: 63%
“…This compared to 58% of the arsenic being bound to PCs, as determined by HPLC-ICP-MS. At least for As(III)-PC complexes, it has been demonstrated that the speciation determined in the extract is representative of that found in the plant. Similar measurements have been performed on plants exposed to cadmium [54] and mercury, showing the existence of Cd-PC and Hg-PC complexes in vivo [55].…”
Section: Hplc-esi-ms/msmentioning
confidence: 70%
“…After the clover was cultured in medium containing mercuric chloride and the mercury in roots were analyzed using differential centrifugation, Carrasco-Gil et al found that much mercury in clover roots is located in cell wall [24]. This result was gotten using homogenate and differential centrifugation.…”
Section: Discussionmentioning
confidence: 97%